Carbon Credit Trading: A Juridical and Fiqh Muamalah Review - Nuradi, Nuradi; Husnul Khatimah; Jaih Mubarok; Muhammad Furqon Almurni (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This paper examines carbon credit trading from both juridical and fiqh muamalah perspectives. Carbon trading as promoted under the Kyoto Protocol and the Paris Agreement, has become a strategic instrument for mitigating climate change by assigning value to verified emission reductions. As interest in environmental finance grows, assessing its alignment with Islamic legal principles is increasingly important. This study employs a qualitative library research method using a descriptive-analytical approach. Data sources include national and international laws, classical and contemporary Islamic legal texts, and academic journal articles relevant to the topic. The findings show that, from a juridical perspective, the Emission Reduction Purchase Agreement (ERPA) positions carbon credit trading within the framework of civil law, especially in contract and property law domains. From the fiqh muamalah perspective, carbon trading can be interpreted through the concept of ijarah bi al-manfa’ah, where the tradable benefit is the certified reduction of emissions. In this context, countries or companies engaged in reforestation or low-emission initiatives provide measurable environmental services to higher-emission entities, who compensate them financially. The study concludes that carbon credit trading, when implemented with transparency and fairness, aligns with both legal and sharia principles. The novelty of this research lies in its integrative analysis, offering a conceptual bridge between modern environmental policy and Islamic commercial jurisprudence, providing insights for regulators, Islamic finance institutions, and policy-makers seeking to develop sharia-compliant environmental instruments.